Therapeutic use of Curd in Digestive Disorders in Ayurveda (AYUSHDHARA, 2023)
Curd, a tasty popular staple diet consisting therapeutic importance too. Chikitsa has mentioned as Aahar (diet), Vihar (regimen) and Aushadhi (Shodhana, Shaman). Curd consists various properties and it is mentioned to include as a diet in diseases as Atisara (diarrhoea), Grahani (malabsorption syndrome), Arsha (haemorrhoids), Peenas (chronic rhinitis). It is found that indication of a curd is commonly mentioned in Ayurveda regarding the digestive disorders. Curd as a diet consists Deepan (appetiser), Ruchiprada (enhancing taste) and Vataghna property. Search had been performed in ancient and modern literature and research publications related to use of a curd in digestive disorders considering probiotic property of a curd. It is easily available and economic. Adding a curd in a diet of patients suffering from digestive disorders is beneficial for effective recovery. The important significance of therapeutic use of probiotics is prevention and treatment of gastrointestinal diseases. This article is a review of available literature related to research question to enlighten role of a curd in digestive disorders. The study was planned for having focused information related to digestive disorders only with preventive, promotive and therapeutic use. Observations are suggesting that curd is a probiotic source of lactobacillus with a nutritive value. Being the richest source of probiotics, curd offers beneficial and healthy microflora to our alimentary canal. Fermented milk improves diarrhoea by improving and regulating the intestinal microbiota and environment as per research conducted. Habitual consumption of fermented milk containing lactobacillus prevented constipation in Vietnamese children as per mentioned in studied article. The yoghurt has also been associated with a decreased risk of developing colorectal cancer. This review article has emphasised on Aahar Chikitsa in digestive disorders related to use of a curd.